(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article, the author examines the concept of renewable energy. The development of renewable energy is a key factor in the growth of energy and sustainable development of the Republic of Kazakhstan. Renewable energy sources – energy sources is continuously renewed by natural processes, including the following types: solar energy, wind energy, hydrodynamic water energy; Geothermal energy: heat the soil, groundwater, rivers, reservoirs and anthropogenic sources of primary energy: biomass, biogas and other fuel from organic waste used to produce electricity and (or) thermal energy. Key words: ecology, law, law, environmental protection, renewable energy.